Development Of A Public Complaint Website At The Women's Empowerment, Child Protection And Family Planning Service Of Jember Regency - Shodik, M. Bahrush; Agustina, Tria; Cahyanto, Triawan Adi (Journal Of Humanities Community Empowerment, 2024)
The Office of Women's Empowerment, Child Protection, and Family Planning (DP3AKB) of Jember Regency is crucial in addressing women, children, and family planning issues. This study aims to develop an effective and accessible public complaint website. The methods used include needs analysis through interviews and literature studies, data design using BPMN, website page programming implementation, and black box testing. The test results show that all basic website features function well, improving efficiency, transparency, and accountability in handling complaints. Users can easily submit complaints, monitor their status, and receive responses from DP3AKB. The conclusion is that this website meets user needs and provides significant benefits to DP3AKB Jember Regency. Further development suggestions include integrating mobile applications and real-time notifications to enhance functionality and ease of use. With this system, handling issues faced by women and children and family planning in Jember Regency can be more effective and efficient.